PERAN GREEN AWARENESS DALAM MEMEDIASI GREEN MARKETING TERHADAP GREEN REPURCHASE INTENTION - Ilham Cahyo Triwibowo; Liana Mangifera (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2024)
The purpose of this study was to analyze the role of green awareness in mediating green marketing on green repurchase intention. The method used in this research is a quantitative method with 153 respondents. The population in this study is the general public of Indonesia. The sampling technique used is purposive sampling, the data used is promer data obtained through respondents' answers using a closed type interview or questionnaire. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software PLS-SEM analysis consists of two Outer model and Inner model. The results of this study indicate that green awaereness is able to mediate the relationship between green brand attachment and green brand trust on repurchase intention but green awaereness is not able to mediate the relationship between green brand image on repurchase intention. This means that even though the green brand image increases, it does not necessarily affect consumer decisions to make repeat purchases.